Histopathological Assessment of Subacute Doses of Tebuconazole on Hepatotoxicity in Rats - Amir Saeed Goudarzi; Masoud Ghorbani; Hadi Esmaeili Gouvarchin Ghaleh; Bahman Jalali Kondori (Negah Institute for Scientific Communication, 2022)
Introduction: Tebuconazole is a systemic fungicide whose toxicity has been reported in animals and humans due to direct and indirect exposure. Our study aimed to assess the hepatotoxic effects of tebuconazole at subacute doses in rats. Methods: Tebuconazole was administered by oral gavage at doses of 6, 12, 25, 50, and 100 mg/kg daily. Serum levels of ALT, AST, and ALP were determined. Histopathological analysis was performed using liver sections stained with hematoxylin and eosin. Parameters such as cell inflammation, accumulation of lipid vacuoles, and hepatocyte necrosis were assessed.  Results: The results showed that the serum levels of AST, ALT, and ALP enzymes elevated in all Tebuconazole doses compared to the control group. This elevation was statistically significant in the 50 and 100 mg/kg groups compared to the control group. Histopathological results revealed the increased necrosis and destruction of hepatocytes and accumulation of lipid vacuoles in the study groups compared to the control group. Conclusion: The study's results showed significant hepatotoxic effects at subacute doses of tebuconazole. These results are alarming in the widespread use of tebuconazole as a fungicide. It is recommended to take the necessary precautions, including wearing gloves or a mask.